Filariasis yang disebabkan oleh Brugia Malayi nonperiodik pada pendatang lama Bugis dan Banjar di Kalimantan Timur - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT Nonperiodic form of B. malayi was recently discovered as a new infraspecific variant (new subspecies) of filarial parasite found among Dayak Indigenous people living scattered in deep forest of East Kalimantan. In this research, clinical or blood (including membrane filter concentration method) examinations were carried out on Bugis or Banjar tribais in kampongs or more open areas in East Kalimantan. The malayan filariasis infections were detected among them, but not in high prevalence nor microfilarial density, such as found in two villages in Mahakam delta or another one In Bontang area, Kutai regency. The clinical manifestations, however, were not severe nor specific.